2007
DOI: 10.1189/jlb.1106698
|View full text |Cite
|
Sign up to set email alerts
|

Skewed expression and up-regulation of the IL-12 and IL-18 receptors in resting and activated CD4 T cells from HIV-1-infected patients

Abstract: IL-12 and IL-18 synergistically induce the production of IFN-gamma by resting and activated T cells. To evaluate whether this induction was affected in HIV-1-infected patients, PBMC or isolated CD4 T cells were cultured with IL-12 plus IL-18, anti-CD3 plus anti-CD28, or PHA for 72 h. Cell samples were labeled daily to assess the levels of IL-12 receptor beta1 (IL-12Rbeta1), IL-12Rbeta2, and IL-18Ralpha. Culture supernatants were analyzed for the presence of Th1- and Th2-related cytokines by ELISA or cytometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Finally, we have previously observed that IL-12 and IL-18 receptors are upregulated in CD4 + T resting lymphocytes of HIV-1-infected patients, suggesting that deregulation of the IL-12 and IL-18 pathways may play a role in the immunopathogenesis of HIV-1 infection (19). It is tempting to think that IL-12 and IL-18 signaling may link cell polarization to HIV-1 susceptibility through the regulation of SAMHD1.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we have previously observed that IL-12 and IL-18 receptors are upregulated in CD4 + T resting lymphocytes of HIV-1-infected patients, suggesting that deregulation of the IL-12 and IL-18 pathways may play a role in the immunopathogenesis of HIV-1 infection (19). It is tempting to think that IL-12 and IL-18 signaling may link cell polarization to HIV-1 susceptibility through the regulation of SAMHD1.…”
Section: Discussionmentioning
confidence: 97%
“…Culture of activated cells with IL-12 resulted in upregulation of the IL-12R2 chain suggesting that treatment with IL-12 may serve to recapitulate IL-12R levels and thus IL-12 responses (Jones, Young et al, 2003). In contrast, a recent study demonstrated that unstimulated CD4 T cells from HIV-1 positive patients expressed a two-fold increase of IL-12R 1 subunit compared with cells from HIV-1 negative controls (de Arquer, Pena et al, 2007). Similar to Jones et al (2003), this group found that stimulation of the CD4 T cells with IL-12 resulted in the enhancement of IL-12R2.…”
Section: Il-12 and Hiv Infectionmentioning
confidence: 99%
“…However, some studies have shown dysregulated expression of other related subunits. For example, dysregulated IL-12 receptor (homologous to gp130) expression has been detected in the setting of HIV infection [19], [20] and common variable immunodeficiency [22], whereas upregulated gp130 expression has been detected in lymphoid tissues of HIV-infected patients at different stages of disease progression [21]. Interestingly, this study identified the IL-27 receptor chain, gp130, as a novel IL-27-responsive gene in human monocytes.…”
Section: Discussionmentioning
confidence: 78%
“…Deregulation of cytokine receptor expression during HIV infection has been previously demonstrated in lymphoid and myeloid cells [19], [20], [21]. Currently, no studies have investigated how HIV affects expression of the unique IL-27 receptor subunit, WSX-1.…”
Section: Discussionmentioning
confidence: 99%